If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + -6y = -2 Solving 5x + -6y = -2 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '6y' to each side of the equation. 5x + -6y + 6y = -2 + 6y Combine like terms: -6y + 6y = 0 5x + 0 = -2 + 6y 5x = -2 + 6y Divide each side by '5'. x = -0.4 + 1.2y Simplifying x = -0.4 + 1.2y
| y^2-3y-10=-1 | | f(x)=1x^2 | | (x^(4/3))+(2x^(2/3))-24 | | 3.75=3x^2-3 | | f(x)=2-x^2 | | -x^2-50x+144=0 | | -x^2-50Q+144=0 | | 6x-2=3x+11 | | s^3-8= | | -2t/3t=22 | | 2c^2-3=5c | | 2m-n/4m-2n | | -2c^3d^2*-3c^3d^3= | | 11+5=9x+11 | | 4y/y^2-1+y-1/y+1 | | 2m/4 | | 3x^2+27x+24= | | x^2(1/2x^2)(10x^-9) | | 3/5-28/56 | | x(5x-29)=42 | | 6-6x-3=-2+3x-13 | | 35=(r-2) | | Y^4-6y-4=0 | | 5(-4+2x)-(8x-12)=68 | | 0.4(8-0.2)= | | (-2k^5f^4)(-5k^2f^5)= | | (5/3)^-2 | | 0.4(8-2x)=-4 | | x+115=180 | | y^2-6y=5-6y^2 | | H(t)=-16t+1000t | | n=0.16/40 |